Considering the Carbon Penalty Rates to Optimize the Urban Distribution Model in Time-Varying Network. (3rd June 2022) - Ji, Yuanyuan; Ji, Shoufeng; Ji, Tingting
Abstract : The existing urban distribution model does not consider both the environmental influence and time-varying factors. This paper studies the urban distribution optimization model considering both time-varying network factors and carbon emission factors and constructs the single period time-varying network urban distribution optimization model and cross-period time-varying network urban distribution optimization model. In this paper, the time-varying network in urban distribution is mathematically described and calculated. By considering the carbon penalty rate, the distribution optimization model is analyzed to formulate the optimal urban distribution scheme for enterprises. An improved variable neighborhood search (VNS) heuristic algorithm is designed to solve the model. The numerical example demonstrates that the higher the carbon emission cost, the greater the carbon penalty rate. When the carbon emission cost increases by 50%, the total cost of the distribution scheme considering carbon emission is saved by 1.21%. The numerical analysis also finds that only when the unit carbon emission cost is higher than 2.937, the carbon penalty rate will stimulate enterprises to reduce emissions.